Contraceptive practices and awareness of emergency contraception among Muslim women of urban slum of Raichur, Karnataka - Ade, Anju D.; Patil, Ramesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: According to NFHS-2005, prevalence of female sterilization is lowest among Muslims (21 percent). Many women prefer not to use contraception and continue childbearing until they have at least one son. Proper use of family planning methods is the key to preventing unplanned pregnancies. This study aimed to assess the contraceptive practices and awareness about emergency contraception among 82 married Muslim women in the reproductive age group. Methods: A cross-sectional study was done in an urban slum area, Raichur where all the Muslim married women in the reproductive age group, attending OPD at UHC, during between August and September 2013 were interviewed using a pre-tested and pre-structured questionnaire. Privacy, anonymity and confidentiality were maintained throughout the process of this study. Results: Out of total 82 Muslim ever married women, majority of them were literate, 63 (76.8%). 50 (61.0%) of women had family size less than or equal to 5. 44 (53.7%) were married at 16-19 years of age and 8 (9.8%) women married between 12-15 years of age which is below legal age of marriage. Maximum total numbers of births were 3-4. Those who wanted male child had births between 5-6. Majority of women 34 (41.5%) had a birth interval of 1 year and 19.5% women had no birth interval. 32 (39.0%) women didn’t use any contraceptive till they completed family. 71 (86.5%) women were aware of all the methods of contraception. Majority of women 30 (36.6%) received information from doctors. Only 11 (13.4%) women were aware of Emergency Contraception. Conclusions: Despite 76.8% literacy and 86.5% of awareness of the various methods of contraception, contraceptive practices were low among women. 32 (39.0%) women didn’t use any contraceptive till they completed family. There is a gap between awareness and practice. Awareness of emergency contraception is quite low among women (13.4%). Emphasis has to be laid on delaying marriage and first pregnancy and education on planning and spacing children and reproductive contraceptive options, especially emergency contraception since all contraceptive methods can have potential failure; the use of emergency contraceptive of plays an important role in preventing unplanned pregnancies. There is a need to improve women’s education about EC. The primary health care providers can play a major role in informing their patients about emergency contraception.